Handbook of optics - Optical Society of America (New York : Mc Graw Hill, 1996)
This CD-ROM covers all topics about optics sources, detectors, detection and processings by human vision and many others. Entire contents of volume 1& 2 (2nd ed.) could be accessed in one cd-rom.
Systems requirements : IBM 386 or compatible PC, 4 MB of RAM, Windows 3.1, Windows 95 or later, CD-ROM drive.
Keywords: Optic -- Handbooks, manual, etc